El concepto de persona a la luz del Vaticano II. Una reflexión desde el Derecho - Carrodeguas Núñez, Celestino (Estudios eclesiásticos, 2007)
Obviously we can approach the reflection on the person from different ways and there are various disciplines which deal with the person. Philosophers, theologians have been reflecting on the human being and each of the different streams of thought has reached its own assessment. In order to arrive at the ultimate foundations of the origin of the human dignity it is necessary to understand that «the mystery of man is made clear only in the mystery of the Incarnate Word», as Gaudium et Spes (n.22) reminds us.